2018
DOI: 10.7441/joc.2018.01.03
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Knowledge Management Systems and Event-B Modelling in a Lean Enterprise

Abstract: This paper provides a case study describing an approach to improving the efficiency of an information system (IS) by supporting processes outside the IS, using the ontology-driven knowledge management systems (KMS) as a mini-application in the area of so-called lean enterprise. Lean enterprise is focused on creating a maximal value for final customers while eliminating all kinds of waste and unnecessary costs, which significantly helps to increase the level of its competitiveness. It is about managerial decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…This is deemed important since it can result in sustainable competitive advantage, as a favorable context for knowledge sharing can contribute to improved operational performance (Manesh et al, 2021;Cassia et al, 2020). Additionally, the literature highlights the importance of knowledge sharing during transition periods, and thus, KM can act as a facilitator for I4.0 implementation (Buřita et al, 2018;Shadi 2017;Cassia et al, 2020). Finally, learning is regarded as a research opportunity both at the group and the individual levels, and it is linked to workers development, which includes training to I4.0, and I4.0 technology effects on individual and group learning (Manesh et al, 2021;Sartori et al, 2022;Oztemel & Gursev, 2020).…”
Section: Research Opportunities Relating Knowledge Management and I40mentioning
confidence: 99%
“…This is deemed important since it can result in sustainable competitive advantage, as a favorable context for knowledge sharing can contribute to improved operational performance (Manesh et al, 2021;Cassia et al, 2020). Additionally, the literature highlights the importance of knowledge sharing during transition periods, and thus, KM can act as a facilitator for I4.0 implementation (Buřita et al, 2018;Shadi 2017;Cassia et al, 2020). Finally, learning is regarded as a research opportunity both at the group and the individual levels, and it is linked to workers development, which includes training to I4.0, and I4.0 technology effects on individual and group learning (Manesh et al, 2021;Sartori et al, 2022;Oztemel & Gursev, 2020).…”
Section: Research Opportunities Relating Knowledge Management and I40mentioning
confidence: 99%
“…Knowledge sharing is also important in transitory periods, for example, to sustain worker knowledge through termination and recruitment. KM-based tools are a strategic component of LM implementations (Buřita, Hrušecká, Pivnička & Rosman, 2018;Shadi, 2017).…”
Section: The Relationship Between Knowledge Management and Lean Manuf...mentioning
confidence: 99%
“…application to Six Sigma projects (Baral, Kifor & Bondrea, 2014), Supply Chain Management (Liu, Leat, Moizer, Megicks & Kasturiratne, 2013), outsourcing (Gong & Blijleven, 2017), information systems (Buřita, Hrušecká, Pivnička & Rosman, 2018;Fiechter, Marjanovic, Boppert & Kern, 2011), and in the service sector services (Zhao, Rasovska & Rose, 2016). However, integration of KM and LM in Manufacturing has only been explored in a limited sense in academic literature, which has highlighted the need for such studies, especially in the context of different industry sectors or types of production systems (Gong & Blijleven, 2017;Shadi, 2017;Gowen III, Stock & McFadden, 2008), and KM-LM assessment.…”
mentioning
confidence: 99%
“…Therefore, from a quality viewpoint, monitoring this parameter is crucial, especially due to the development of modern manufacturing techniques (e.g., VATRM, out-of-autoclave (OaA), automated prepreg laying, etc.) introducing lower production costs and shorter manufacturing times [23,24]. For example, Kedari et al [25] suggested to increase mould temperature and vacuum and appropriately reduce inlet pressure to produce high quality VARTM parts.…”
Section: Introductionmentioning
confidence: 99%